2011
DOI: 10.1002/adfm.201100266
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Atomic Disorder in Biogenic Carbonate Hydroxyapatite Using the Infrared Spectrum Grinding Curve Method

Abstract: Biogenic carbonate hydroxyapatite crystals are inherently disordered at the atomic level due mainly to the substitutions of various ions in the crystal structure, and, in the case of the bone family of materials, to the fact that these very small crystals have a very large surface‐to‐bulk ratio. Characterization of the extent of disorder is of much interest, as this relates to the stability and hence solubility of the crystals. Here the infrared spectrometry grinding curve approach developed for calcite, is ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 34 publications
(43 reference statements)
0
24
0
2
Order By: Relevance
“…A more rapid degradation of collagen will facilitate further exchange between soil carbonate and bioapatite. Furthermore, recent infrared spectroscopic evidence showed that there were differences in crystallinity among different mammal species (Asscher et al, 2011). Although Asscher et al (2011) did not sample fish or turtle bone, they found that human enamel was more crystalline than any other mammal tested.…”
Section: Diagenesismentioning
confidence: 95%
See 1 more Smart Citation
“…A more rapid degradation of collagen will facilitate further exchange between soil carbonate and bioapatite. Furthermore, recent infrared spectroscopic evidence showed that there were differences in crystallinity among different mammal species (Asscher et al, 2011). Although Asscher et al (2011) did not sample fish or turtle bone, they found that human enamel was more crystalline than any other mammal tested.…”
Section: Diagenesismentioning
confidence: 95%
“…Furthermore, recent infrared spectroscopic evidence showed that there were differences in crystallinity among different mammal species (Asscher et al, 2011). Although Asscher et al (2011) did not sample fish or turtle bone, they found that human enamel was more crystalline than any other mammal tested. A lower crystallinity implies that apatite is more likely to either exchange carbonate with carbonate present in the environment of the grave, or dissolve and re-precipitate new apatite containing exogenous carbonate.…”
Section: Diagenesismentioning
confidence: 95%
“…The prevalence of Fe-Mn oxides and absence of pyrolized collagen in dark-coloured bones indicate that bone colouration is due to post-depositional staining rather than burning (Nir 2016). Calculated values of the infrared bone crystallinity index (IRSF; Weiner and Bar-Yosef 1990) were plotted in reference to the full width at half maximum of the hydroxylapatite main absorbance band at 1030 cm −1 , following Asscher et al (2011) (Fig. 10).…”
Section: Bonesmentioning
confidence: 99%
“…Globalmente hay un amplio conjunto de trabajos sobre microscopía aplicada al análisis de las termoalteraciones (Nicholson 1993, Koon et al 2003, Koon et al 2010Lebon et al 2008, Weiner 2010, Asscher y Boaretto 2011, Nevin et. al.…”
Section: Antecedentesunclassified
“…Cuando se graficaron los valores SF y FWHH, fue posible generar líneas de tendencia que reflejaron el efecto del tamaño de la partícula. Adicionalmente, con la ubicación en la gráfica del FWHH y el SF, fue posible evidenciar los efectos de desorden atómico (Asscher et al 2011).…”
Section: Para Realizar La Curva De Molido O Grindingunclassified